Multi-locus Sequence Typing of Staphylococcus aureus isolated from different Clinical Isolates - Falah H Abbas; Adnan H Aubaid (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To evaluate the prevalence and genetic diversity of Staphylococcus aureus (S.aureus) isolates from different clinical samples using Multilocus Sequence Typing (MLST), with special attention to identification of clonal lineages and their associated resistance and virulence genes. METHODOLOGY: A cross-sectional observational study consisted of 301 clinical specimens, including throat swabs, urine samples, wound swabs, and burn swabs, collected from patients presenting with varying illnesses and attending the Al-Dewaniyah Teaching Hospital, Al-Dewaniyah province, Iraq, from January to March 2025. Isolation of S. aureus was performed using Mannitol Salt Agar, and the VITEK 2 system was used for corroborative identification. Three to four isolates underwent MLST. Patients with an age range between 18 and 60 years who presented with various illnesses and signs of pyogenic infections were included. Patients with other infections or chronic diseases, and those under 18 years old, were excluded. RESULTS: Out of 301 samples, 56 (18.60%) tested positive for S. aureus. The highest prevalence was found in burn (21.88%) and throat (21.05%), followed by urine (16.51%) and wound (16.92%). Statistical analysis showed no significant association between sample type and S. aureus prevalence (p = 0.82). MLST identified distinct lineages: ST5/CC5 (throat, HA-MRSA), ST8/CC8 (urine, USA300 CA-MRSA), ST30/CC30 (wound, Southwest Pacific clone), and ST45/CC45 (burn, European CA-MRSA). These results demonstrate significant genetic heterogeneity, with both HA- and CA-associated strains present. CONCLUSION: The study highlights the genetic diversity and presence of S. aureus, including high-risk Methicillin-Resistant S. aureus (MRSA) clones such as ST5 and ST8, in various clinical specimens.